MENYELARASKAN ARAH PEMBANGUNAN PENDIDIKAN KHUSUS DI INDONESIA - Totok Bintoro (Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2007)
This article is of the opinion that quality improvement of Special Education in Indonesia is slow due to ( a) perception of public and the Government assuming that education of students with special needs is less important, ( b) wrong perception about Special Education regarding special education is for handicapped children only,( c) incorrect orientation in the education management which gives priority to intellectuality aspect, ( d) management of Special Education by segregation , ( e) policy in the management of national education using approach of education production function or input-output analysis which is not executed consequently, ( f) management of education is executed in bureaucratic centralization ( g) education service paying less attention to individual requirement of students, and ( h) human resource in Special Education still has to be improved. After analyzing the existing conditions critically from various aspects, this article provides a set of recommendations, mostly concerning with policy at national and regional levels.